Fatigue Levels and it is Impacts on Physical, Cognitive and Psycho-social Wellbeing in Patients with Breast Cancer Undergoing Chemotherapy - Athbi, Hassan Abdullah; Rukaya Aqeel Hassan; Ayam Abbas Ali; Baneen Fadhil Khudhr; Hussein Khelf Kitab (Indonesian Journal on Health Science and Medicine, 2025)
Fatigue is a highly prevalent and debilitating symptom among patients with breast cancer undergoing chemotherapy, profoundly affecting multiple dimensions of health and functioning. Chemotherapy-related fatigue in this population negatively influences physical capacity, cognitive performance, and psychosocial well-being, yet its multidimensional impact within the Iraqi clinical context remains insufficiently examined. Few studies have comprehensively evaluated the combined physical, cognitive, and psychosocial consequences of fatigue among Iraqi breast cancer patients, nor assessed its associations with demographic and clinical characteristics. This study aimed to determine the levels of fatigue and examine its impact on physical, cognitive, and psychosocial domains among patients with breast cancer receiving chemotherapy. A descriptive study of 106 female patients at Imam Al-Hussein Oncology Center revealed that 71.7% experienced severe fatigue and 28.3% moderate fatigue. The overall mean fatigue score was high (MS = 4.0). Fatigue showed severe impact across all domains, with 96.2% of patients classified within the severe-impact category. Physical limitations included muscle weakness, reduced functional ability, and increased need for rest; cognitive impairments involved diminished alertness, reduced attention, and slowed thinking; psychosocial effects included decreased motivation, social withdrawal, and emotional distress. A significant association was found between fatigue level and the three impact dimensions (p = 0.003). This study provides one of the first multidimensional assessments of chemotherapy-related fatigue among Iraqi breast cancer patients. Routine fatigue assessment and multidisciplinary management are essential to mitigate its extensive effects and improve quality of life for patients undergoing chemotherapy. Highlights Severe fatigue was highly prevalent among breast cancer patients undergoing chemotherapy, affecting 71.7% of the sample. Fatigue had a significant negative impact on physical, cognitive, and psychosocial functioning, with 96.2% experiencing severe impairment. A strong association was found between fatigue severity and multidimensional functional decline (p = 0.003).